Short Communication: Javan Leopard Cat (Prionailurus bengalensis javanensis Desmarest, 1816) in the Cisokan non-conservation forest areas, Cianjur, West Java, Indonesia - SYA SYA SHANIDA; RUHYAT PARTASASMITA; TEGUH HUSODO; PARIKESIT PARIKESIT; ERRI NOVIAR MEGANTARA (Society for Indonesian Biodiversity, 2018)
Shanidah SS, Partasasmita R, Hudoso T. Parikesit, Meganatara EN. 2018. Short Communication: Javan Leopard Cat (Prionailurus bengalensis javanensis Desmarest, 1816) in the Cisokan non-conservation forest areas, Cianjur, West Java, Indonesia. Biodiversitas 19: 37-41. Javan Leopard Cat (Prionailurus bengalensis javanensis Desmarest, 1816) in the Cisokan non-conservation forest areas, Cianjur, West Java, Indonesia. Biodiversitas 19: xx, xxx.There is no accurate data about the number of leopard individuals in Java Island in both conservation and non-conservation areas. Besides, human continue to deforestation for the necessities of life, such as agriculture, plantation, etc. Therefore, it is important to research about the existence of leopard cat in Cisokan of Cianjur Regency. The aim of this research is to investigate evidence of the leopard cat’s existence, encounter rate of leopard cat and estimation of leopard cat individual in the non-conservation forest areas, Cisokan, Cianjur. Indirect observation sign survey and direct observation with camera trap were carried out to find evidence of the existence of leopard cat (feces and footprint). The results of the study showed that the evidence of leopard cat’s existence are 6 footprints, 27 feces, and 1 individual which was able to observe. The encounter with camera traps was 29.16 independent detections /100 camera days, resulting in 7-12 estimated individuals.